The cancer-associated microprotein CASIMO1 controls cell proliferation and interacts with squalene epoxidase modulating lipid droplet formation - Polycarpou-Schwarz, Maria; Schott, Johanna; Rom, Joachim; Aulmann, Sebastian; Sinn, Peter; Diederichs, Sven (Oncogene, 2018)
Breast cancer is a leading cause of cancer-related death in women. Small open reading frame (sORF)-encoded proteins or microproteins constitute a new class of molecules often transcribed from presumed long non-coding RNA transcripts (lncRNAs). The translation of some of these sORFs has been confirmed, but their cellular function and importance remains largely unknown. Here, we report the identification and characterization of a novel microprotein of 10 kDa, which we named Cancer-Associated Small Integral Membrane Open reading frame 1 (CASIMO1).
Gesehen am 23.04.2020